THE EFFECT OF BITTER MELON FRUIT EXTRACT (MOMORDICA CHARANTIA L.) SUPPLEMENTED WITH SNAKEHEAD FISH POWDER (CHANNA STRIATA) ON CLINICAL IMPROVEMENT OF DIABETIC ULCERS: A RANDOMIZED CONTROLLED TRIAL - ROSYID, FAHRUN NUR; MUHTADI; SUHENDI, ANDI; SUGIHARTO, SH; SUSWARDANY, DWI LINNA; SARI, DWI ROSELLA KOMALA; RAHMAN, AHMAD FADHLUR (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aims to examine supplementation of a combination of bitter melon extract with snakehead fish powder for clinical improvement of diabetic foot ulcers (DFU). Methods: This study used a randomized, double-blinded, placebo-controlled trial. A total of 50 DFU patients who met the criteria were divided into 2 groups, namely: 25 patients as the treatment group were given supplementation of bitter melon extract combination with snakehead fish powder and a control group of 50 patients who received a placebo. This intervention was carried out for 4 w. DFU clinical improvement was measured with perfusion, extent, depth, infection, sensation (PEDIS) scores at baseline, weeks 2, 3, and 4. Data were analyzed using a generalized linear model (GLM) and post hoc. Results: After 4 w of treatment, the PEDIS score of the treatment group in week 1 decreased in week 2 (6.48±1.19), significantly (p = 0.003), decreased in week 3 (5.64±1.18) and significantly (p = 0.0001), decreased in week 4 (4.28±1.06) and was significant (p = 0.0001), while the control group in week 1 decreased in week 2 (5.68±2.30), but not significant (p=0.574), decreased for week 3 (5.52±2.23), but not significant (p=0.161), decreased for week 4 (5.28±2.13) and not significant (p=0.056), and there was an effect of supplementation with a combination of bitter melon extract and snakehead fish powder on the PEDIS score (p=0.004). Conclusion: Supplementation of a combination of bitter melon extract with snakehead fish powder significantly reduced PEDIS Score on DFU patient and has an effect on clinical improvement.